Number Mussels as a Medium for Learning to Count for 5 - 6 Years Old - Kiromiyah, Zulfatul; Widjayatri, RR. Deni (Jurusan Pendidikan Islam Anak Usia Dini, 2024)
This study explores the effectiveness of using number mussels as an educational medium to develop counting skills in children aged 5–6 years. Numeracy represents a fundamental cognitive ability that supports problem-solving and daily life activities. However, children’s mathematical understanding often varies depending on genetic, environmental, and experiential factors. To address these differences, this research implements a qualitative classroom action approach conducted at PAUD Hidayatul Mustafid, Tangerang-Banten. Ten students participated in learning activities using the number mussel tool, which integrates numbers, colors, and sizes to stimulate children’s cognitive and fine motor development. Data were collected through observation, documentation, and evaluation, and analyzed using the Revised Bloom’s Taxonomy as an assessment framework. The results demonstrate that the number mussel medium effectively enhances children’s critical, creative, collaborative, and communicative abilities. Participants actively engaged in identifying numbers, performing simple arithmetic operations, and recognizing color and size variations. Overall, the use of number mussels proved to be an effective and engaging learning tool for developing early numeracy skills while simultaneously fostering social interaction and physical coordination among preschool learners.